Inovasi Pembelajaran PjBL untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa - Abidin, Zainal; Syahrir, Syahrir; Sukarma, I Ketut; Masjudin, Masjudin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop a Project-Based Learning (PjBL) instructional device integrated with concrete media to enhance students' mathematical problem-solving abilities. This research uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate), conducted at SMPN 3 Kopang, involving 25 seventh-grade students. The developed devices include Lesson Plans (RPP), Student Worksheets (LKS), and Mathematical Problem-Solving Ability Tests. The results of validation by two validators show that the devices are highly valid, with average Skores exceeding 90%. The practicality of the device, based on teacher responses, shows a Skore of 92.5%, indicating that the device is easy to use in teaching. The effectiveness of the device was measured through pretest and posttest problem-solving ability Skores, with an N-Gain of 71.66%, demonstrating a significant improvement in students' mathematical problem-solving skills. Based on these results, it can be concluded that the PjBL instructional device integrated with concrete media is valid, practical, and effective in enhancing students' mathematical problem-solving abilities. This study is expected to contribute to the development of more interactive and applied mathematics learning.